Episodic memory must be grounded in reality in order to be useful in communication. (22nd January 2018) - Blank, Hartmut
Abstract: The primary function of episodic memory is to provide reliable information about reality that is essential for surviving and navigating in an environment. The communicative function of episodic memory "sits on top of" this basic function but does not, in itself, explain it in its totality (but may explain particular aspects such as its sensitivity to source credibility).